Precision disease management: prognostic biomarker for chronic lung damage in long COVID - Oo, Adrian; Chu, Justin Jang Hann (ERJ open research, 2024)
Early detection of potential severe disease progression facilitates implementation of relevant precise disease management strategies. MMP-7 is a reliable prognostic biomarker for long COVID persistent lung damage that should be considered for clinical use. https://bit.ly/3Ccxozg.Early detection of potential severe disease progression facilitates implementation of relevant precise disease management strategies. MMP-7 is a reliable prognostic biomarker for long COVID persistent lung damage that should be considered for clinical use. https://bit.ly/3Ccxozg.